Knowledge Management ( KM ) A New Management Paradigm in M.I.N.T - Ab. Hamid, Amy Hamijah binti; Aminuddin, Rapieh; Sharifuldin Salleh, Mohd Amin (The Asian Journal of Technology Management (AJTM), 2008)
Knowledge management (KM) is one of the leading approaches used for organizationalimprovement in which a range of specific processes and practices for identifying, capturing,acquiring, organizing and preserving knowledge and for making it available for transfer, sharingand reuse across the organization are being used. KM can help research and development (R&D)organization to intensify innovation by using information and communication technology (ICT) tofacilitate the knowledge flow. Even though KM is a new management paradigm in MINT, the KMstructure, policy, objectives, strategies and initiatives has been established. However implementationrate is rather slow and the impact of KM initiatives is not readily felt. This paper has identified andcompared KM case studies. These are analysed and assessed based on their challenges, strategiesand lesson learnt from an ICT perspective. The analysis and assessment of the case studies is used todevelop action plans to improve MINT KM implementation. The result of this analysis andassessment will be proposed as MINT KM solution in the future.Keywords: knowledge management, knowledge management process framework, knowledge creationspiral model, knowledge management life cycle, knowledge management processes cycle